Quantitative Analysis of Sibutramine Hydrochloride in Slimming Herbal Medicines in Banda Aceh Using UV-Vis Spectrophotometry - Ruhul Maghfirah; Farida, Mutia; Purnama, Agnia; Afifi, Muhammad Ridho; MZ, Kartika; Rahmawati, Erda (JURNAL BIOLOGICA SAMUDRA, 2025)
Sibutramine hydrochloride is a chemical compound that was once often used as a weight loss drug. This drug is hazardous if used illegally in herbal medicine because it can cause health problems such as kidney failure, heart attacks, and strokes. BPOM has banned its use in herbal medicine, but until now herbal medicine containing sibutramine hydrochloride is still on the market. This study aims to determine the levels of Sibutramine Hydrochloride contained in slimming herbal medicine. The samples used in this study consisted of four brands of slimming herbal medicine that are not registered with BPOM, coded A, B, C, and D, which were obtained from several shops in Baiturrahman District, Banda Aceh City. Sampling was carried out using the total sampling method and then analyzed quantitatively using UV-Vis spectrophotometry. The results of the analysis showed that the four samples were positive for containing Sibutramine Hydrochloride with an average level of 31.69% of herbal medicine sample A; 39.88% of herbal medicine sample B; 7.09% of herbal medicine sample C; and 36.60% of herbal medicine sample D. Therefore, stricter examination and supervision of the circulation of slimming herbal medicine products in the Banda Aceh city area are needed to protect public health.